349 DETERMINANTS OF URINARY CALCIUM AND URIC ACID EXCRETION IN CHILDREN AFTER RENAL TRANSPLANTATION. (1st January 2006) - Peterson, J. M.; Butani, L.
Abstract : Excess urinary calcium and uric acid excretion predispose patients to problems such as hematuria and nephrolithiasis. The natural history of and risk factors for hypercalciuria (HC) and hyperuricosuria (HU) have not been studied in the pediatric renal transplant population, which may be at greater risk of complications related to these abnormalities. The purpose of our study was to define the prevalence of HC and HU after renal transplantation (Tx) and to determine independent predictors of urinary calcium and uric acid excretion. Twenty-five consecutive pediatric patients who had renal transplants performed at our center were serially studied between 1 and 12 months after Tx. Demographic data and data on the random urinary calcium to creatinine ratio (Uca/cr) and uric acid excretion were collected. Data were analyzed using the S-PLUS software. Simple descriptive statistics and the multivariable mixed effects general linear model were used for data analysis. Statistical significance was set at a p value < .05. The median age range of the patients was 10.6 years; 14 (56%) were male. The prevalence of HC (Uca/cr > 95th percentile for age) and HU (urinary uric acid > 0.57 mg/dL glomerular filtration rate [GFR]) was 16% and 20% respectively at 1 month and 11% for each at 12 months. The mixed effects general linear model demonstrated male gender to be the only (negative) predictor of the Uca/cr ( p = .0218) and for HC ( p = .0372). GFR was the only predictor for urinary uric acid excretion ( p < .001). The use and dose of corticosteroids had no effect on urinary calcium or uric acid excretion. There was no change in urinary excretion of calcium or uric acid with time after Tx (see Table ). In conclusion our data demonstrates a high incidence of HU and HC in pediatric renal Tx recipients even on long-term follow-up; female patients in our study were found to be at greatest risk of having HC, while patients with low GFR were at risk of having high urinary uric acid excretion. The long-term clinical implication of these metabolic abnormalities remains to be elucidated in prospective trials.